2018
DOI: 10.3390/ani8110203
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Trailer Thermal Environment Experienced by Market Pigs Transported in the US

Abstract: Simple SummaryTransport conditions can be a challenge for pigs being transported to market. In this study, 40 trips of commercial market pigs transported from the farms to an abattoir were monitored for thermal conditions including temperature and relative humidity in order to better understand thermal variability within the trailer during transport. Variation in thermal environment inside the pig transport trailer was used as an indicator of ventilation pattern during various weather conditions. During cold w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Unlike temperature trends in the current study, the trailer section did not affect relative humidity measures during morning and afternoon transport. Xiong et al (2018) found that the humidity and humidity index did not vary among different potbelly trailer sections during mild, warm, and very hot weather conditions. During colder conditions, Morris et al (2021) found that fore and center sections of potbelly and straight-deck trailers had a 4.3%-greater relative humidity than the aft section.…”
Section: Discussionmentioning
confidence: 89%
“…Unlike temperature trends in the current study, the trailer section did not affect relative humidity measures during morning and afternoon transport. Xiong et al (2018) found that the humidity and humidity index did not vary among different potbelly trailer sections during mild, warm, and very hot weather conditions. During colder conditions, Morris et al (2021) found that fore and center sections of potbelly and straight-deck trailers had a 4.3%-greater relative humidity than the aft section.…”
Section: Discussionmentioning
confidence: 89%
“…Considering the time exposed to vibration, our study classifies the driving styles (normal driving style, average VDV total value: 8.5 m s –1.75 ; aggressive driving style, average VDV total value: 9.5 m s –1.75 ). Pigs are exposed to HT and LT during transportation, depending on the weather conditions [ 33 ]. Heat and cold stress can both negatively impact pig mortality and welfare [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xiong, Gates, and Green-Miller [61] (USA) analyzed the effects of the thermal category, trailer zones, and misting method (before the start of the trip) for mild, warm, and hot weather (16.7-35.3 • C) and cold weather (−10.6-7 • C) transport trips of market pigs. They found that the front top and bottom zones were warmer during cold weather than the rest of the trailer, indicating less ventilation toward the front.…”
Section: Methods To Mitigate Defects In Pork and Poultry Meat During ...mentioning
confidence: 99%
“…Wang et al [62] offered another solution to reduce the adverse effects of HS during prolonged (>3 h) pre-slaughter transport of poultry in summer. Supplementation with resveratrol [61] at a dose of 400 mg/kg for 21 days or guanidine acetic acid at a dose of 1200 mg/kg for 14 days [49] before slaughtering broilers exposed to HS can help reduce the rate of glycolysis of PM muscles, which mainly contain glycolytic fibers [63], which can improve meat quality.…”
Section: Methods To Mitigate Defects In Pork and Poultry Meat During ...mentioning
confidence: 99%